Visit to Lower Kamula village in Kenya: Session on Female Empowerment - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Female Empowerment session. The session was held as part of a testing of an upcoming Practitioner’s Guide that will help researchers and development practitioners pick up gender and social differences in communities. It also aspires to help both researchers and community members sort out the needs and strengths of a particular village, useful when planning climate adaptation and mitigation work.